Meningkatkan Pemahaman Analytical Exposition Melalui Metode Think Pair and Share - martini, lina (Komunitas Manajemen Kompetitif, 2017)
Abstract: The ability to improve learning outcomes becomes a target in learning, a learner needs to study seriously and always seriously understand the various subject matter. So far in learning analytical exposition of a learner is still not optimal to achieve it. Through classroom action research by applying think pair and share action and analyzed descriptively, hence obtained result that applying of think pair and share action method can improve ability of analytical exposition in learners. Keywords: think pair and share model, analytical exposition